Research trends in Economic Geography. Bibliometric study of the Web of Science (1920-2020) - Alonso-Logroño, María Pilar; Bautista-Puig, Nuria (Revista de Estudios Andaluces, 2022)
One of the first tasks to tackle any scientific publication is to review all the scientific literature on the subject. This article presents a methodology that allows analyzing scientific trends in a discipline through a bibliometric analysis. Specifically, the field of Economic Geography is used as a case study, Web of Science (WoS) has been chosen as the database for this analysis. With a set of 4,307 publications, various bibliometric indicators are analyzed, such as the evolution of scientific production, the agents involved (countries and organizations) and topics addressed, in order to see the evolution of the scientific output and the thematic specializations of Economic Geography from 1920 to the present.